Design of Reinforced Concrete Structure for The Earthquake-Resistant 9-Story Green Hexa Hotel Using a Dual System in Pontianak: Perancangan Struktur Beton Bertulang Gedung Hotel Green Hexa 9 Lantai Tahan Gempa Dengan Menggunakan Sistem Ganda di Kota Pontianak - Rahmasari, Puspita; Nikita Putri, Asha; Rizaldi; Supardi, Iwan (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Pontianak City is undergoing substantial growth in the tourism sector, as evidenced by the increasing number of tourists annually, making the presence of hotels increasingly crucial. From 2011 to 2019, West Kalimantan itself experienced six earthquakes, making earthquake-resistant building planning a necessity as a mitigation against earthquake disasters. This research aims to obtain a safe and comfortable design for an earthquake-resistant hotel building in Pontianak based on SNI 1726: 2019. The Green Hexa Hotel consists of 9 floors with a total height of 36 m and an area of 1286 m2 using a reinforced concrete structure. The building is designed using SRPMM combined with shear walls. The loading refers to SNI 1727:2020. The structural analysis using ETABS and 2D working drawings using AutoCAD software. All structural components are designed using concrete with the fc' 30 MPa and fy 420 MPa rebar. The design results include a 150 mm solid slab floor and a 120 mm floor slab; 6 types of beams, BI.1 35cmx65cm, BA.1 30cmx50cm, BI.2 30cmx55cm, BA.2 24cmx45cm, elevator beam 24cmx45cm, landing beam 24cmx45cm; 2 types of columns, K.1 60cmx60cm, K.2 40cmx40cm, a type of 30 cm shear wall; 7 types of foundations, P.1 140cmx140cmx50cm, P.2 140cmx260cmx50cm, P.3 260cmx260cmx60cm.